The Democratic Values Included in Sixth Grade EFL Textbooks in Jordan: Analytical Study - Sahm Tayseer Al-Ma'aitah; Majid Muhammad Al-Khataybeh (Britain International for Academic Research (BIAR) Publisher, 2022)
This analytical study aimed at analyzing the democratic values existing in sixth-grade English textbooks in Jordan. The population of the study consisted of all content of sixth-grade EFL textbooks during the scholastic year 2021\2022. The researchers developed a content analysis card consisting of 37 democratic values distributed according to (4) fields: Political Principles, Cultural Rights, Human and Social relations, and Religious Values. The findings revealed that there are 1846 democratic values in the sixth-grade textbooks. The findings also indicated that the political principles are the most frequent value in the content of sixth-grade English textbooks while religious values are the least promoted within the textbooks.